Biological Properties of Structurally Related α-Helical Cationic Antimicrobial Peptides - Scott, Monisha G. (American Society for Microbiology, 1999)
A series of α-helical cationic antimicrobial peptide variants with small amino acid changes was designed. Alterations in the charge, hydrophobicity, or length of the variant peptides did not improve the antimicrobial activity, and there was no statistically significant correlation between any of these factors and the MIC for Pseudomonas aeruginosa, Escherichia coli, or Salmonella typhimurium. Individual peptides demonstrated synergy with conventional antibiotics against antibiotic-resistant strains of P. aeruginosa. The peptides varied considerably in the ability to bind E. coli O111:B4 lipopolysaccharide (LPS), and this correlated significantly with their antimicrobial activity and ability to block LPS-stimulated tumor necrosis factor and interleukin-6 production. In general, the peptides studied here demonstrated a broad range of activities, including antimicrobial, antiendotoxin, and enhancer activities.